2014
DOI: 10.5858/arpa.2013-0236-oa
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity and Microsatellite Instability Are Rare in Sporadic Dedifferentiated Liposarcoma: A Study of 43 Well-Characterized Cases

Abstract: Context.-Defects in mismatch repair proteins have been identified in Lynch syndrome-associated liposarcomas, as well as in rare sporadic sarcomas. However, it is unclear if mismatch repair defects have a role in sarcoma tumorigenesis. Microsatellite instability is a surrogate marker of mismatch repair defects.Objectives.-To determine whether sporadic dedifferentiated liposarcomas display microsatellite instability and, if so, to evaluate whether such instability differs between the lipogenic and nonlipogenic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…67 While a few sarcomas, including leiomyosarcoma and undifferentiated pleomorphic sarcoma, have been associated with Lynch syndrome, liposarcoma is the most frequent. [67][68][69][70][71][72] A prospective study of 658 adults with soft tissue sarcoma revealed that 2.8% of those patients had a genetic syndrome, predominantly Recklinghausen neurofibromatosis and bilateral retinoblastoma. 73 While reports of rhabdomyosarcoma 67 and gastric sarcoma 74 have been identified in patients with Lynch syndrome, no reported cases of cardiac sarcoma or spindle cell sarcoma have been previously reported in patients with either constitutional mismatch-repair deficiency or Lynch syndrome.…”
Section: Sarcoma In Lynch Syndromementioning
confidence: 99%
“…67 While a few sarcomas, including leiomyosarcoma and undifferentiated pleomorphic sarcoma, have been associated with Lynch syndrome, liposarcoma is the most frequent. [67][68][69][70][71][72] A prospective study of 658 adults with soft tissue sarcoma revealed that 2.8% of those patients had a genetic syndrome, predominantly Recklinghausen neurofibromatosis and bilateral retinoblastoma. 73 While reports of rhabdomyosarcoma 67 and gastric sarcoma 74 have been identified in patients with Lynch syndrome, no reported cases of cardiac sarcoma or spindle cell sarcoma have been previously reported in patients with either constitutional mismatch-repair deficiency or Lynch syndrome.…”
Section: Sarcoma In Lynch Syndromementioning
confidence: 99%